2020
DOI: 10.26848/rbgf.v13.07.p3234-3253
|View full text |Cite
|
Sign up to set email alerts
|

Análise Descritiva da Precipitação, Temperatura, Umidade e Tendências Climáticas no Recife - Pe

Abstract: Os efeitos das mudanças climáticas sobre as principais variáveis atmosféricas locais é o objeto deste estudo, a partir de dados de 1961 a 2019 para a localidade do Recife-PE. A metodologia engloba uma análise exploratória e descritiva com distribuição de frequencia por faixas de intensidades pluviométricas e identificação de tendências em escalas temporais diversificadas em meses, quadras, estações, anos e décadas das variaveis precipitação, temperaturas e umidade do ar. Verificou-se redução das precipitações … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…The summer and autumn seasons experienced more pronounced declines, particularly noteworthy is the month of May, which exhibited a reduction of 1.06% per decade. Concerning the probability density of extreme temperature values spanning the period from 1961 to 2019, a likelihood of elevation in both Tmax and Tmin values were detected [34] (Figure 2). The probability curves show that temperature anomalies in Recife are becoming more pronounced and more likely, resulting in an increased probability of heat waves.…”
Section: Main Urban Heat Findings and Public Interventions In Recifementioning
confidence: 99%
See 1 more Smart Citation
“…The summer and autumn seasons experienced more pronounced declines, particularly noteworthy is the month of May, which exhibited a reduction of 1.06% per decade. Concerning the probability density of extreme temperature values spanning the period from 1961 to 2019, a likelihood of elevation in both Tmax and Tmin values were detected [34] (Figure 2). The probability curves show that temperature anomalies in Recife are becoming more pronounced and more likely, resulting in an increased probability of heat waves.…”
Section: Main Urban Heat Findings and Public Interventions In Recifementioning
confidence: 99%
“…The historical meteorological data series from INMET, spanning from the 1960s to 2020 for Recife, were analyzed [34]. Concerning the thermodynamic variables, these authors revealed a trend of increasing annual maximum (Tmax) and minimum (Tmin) temperatures, along with a decrease in annual relative humidity (Ur).…”
Section: Main Urban Heat Findings and Public Interventions In Recifementioning
confidence: 99%
“…No caso da cidade do Recife, a relação entre a cidade e o clima é marcada por conflitos. Do ponto de vista termodinâmico, a temperatura do ar desta cidade reflete nas transformações da superfície e tem se apresentado com a tendência geral de acréscimo ao longo dos últimos anos (MEDEIROS, 2020;GUEDES;SILVA, 2020). Porém, ao considerar a variabilidade espacial da temperatura do ar ao longo da malha urbana, a quantidade de pontos públicos de coleta de dados ainda é insuficiente.…”
Section: Introductionunclassified